Parents' and caregivers' satisfaction with community-based rehabilitation (CBR) services for children with disability in east coast states in Peninsular Malaysia - Hasan, Haliza; Abdul Aziz, Aznida Firzah; Syed Junid, Syed Mohamed Al Junid (Blackwell Publishing Ltd, 2020)
The Community-Based Rehabilitation (CBR) services under the Malaysian Ministry of Women, Family and Community Development have provided two types of services for disabled children: centre-based and home-based care since 1984. A cross-sectional study was conducted among parents and caregivers with children receiving treatment at CBRs on the east coast of Peninsular Malaysia, to determine the level of satisfaction with the services provided. Respondents were recruited via multi-staged sampling, and simple randomisation at CBR level. Respondents self-administered the Physical Therapy Satisfaction Questionnaire (PTSQ) and provided sociodemographic data. A total of 297 respondents were recruited and all the questionnaires were returned complete, making the response rate 100%. Total satisfaction scores and factors influencing respondents’ satisfaction for both groups were analysed. The mean total satisfaction score for centre-based and home-based were 84.69 (SD = 10.01) and 75.30 (SD = 12.23; t = 7.160, p ≤ .001) respectively. Ninety-eight per cent of centre-based and 89% of home-based respondents were satisfied with the current services. There were significantly mean differences in the satisfaction level of respondents of different states respectively (Kelantan mean 84.92 10.83, Terengganu mean 77.49 11.16 and Pahang mean 77.47 12.93, p ≤ .001). Factors associated with satisfaction were education (p = .002), occupation (p = <0.001), monthly income (p = .001) and source of income (p = .001). In conclusion, majority of parents and caregivers were satisfied with current services provided at CBR and satisfaction with services was dependent on CBR centre location and education and financial earning capacity.